Wrought iron gates with Deussua written in large metal letters - Mumbai Archive Project (Jio Institute, 2024)
The association of the club with Deussua village, South Goa district, is evident in the wrought iron gates where Deussua is written in large metal letters, along with Club of St. Anthony.